Students’ Challenges in Implementing Metacognitive Strategies in Reading Authentic German Texts: Evidence from Indonesian Higher Education - Achmad, Abdul Kasim; Ardiyani, Dewi Kartika (Makassar State University, 2026)
This study investigates students’ challenges in implementing metacognitive strategies in reading authentic German texts at Universitas Negeri Makassar. Employing a qualitative descriptive-exploratory design, the study involved 28 B1-level students from the German Language Education Study Program. Data were collected through open-ended questionnaires and Focus Group Discussions (FGDs) and analyzed using thematic analysis to identify recurring patterns in students’ experiences. The results indicate that students tend to employ metacognitive strategies: planning, monitoring, and evaluation, intuitively rather than consciously and systematically. Four major challenges were identified: inconsistent use of planning strategies, difficulties in activating prior knowledge, limited vocabulary (Wortschatz), and difficulties in regulating metacognitive strategies. These findings reveal a gap between theoretical expectations of metacognitive strategy use and actual learner practices, particularly when dealing with authentic texts that require higher cognitive processing. These findings suggest that metacognitive strategies need to be taught explicitly and reinforced continuously to foster students’ metacognitive awareness and improve their comprehension of authentic German texts. Practically, the findings highlight the need for a more systematic integration of explicit metacognitive instruction in reading classes, including structured pre-, while-, and post-reading activities, guided reflection, and targeted support for vocabulary development and activation of prior knowledge, in order to help students manage authentic texts more effectively